Preparation and characterization of tungsten oxide thin films - Ho, Soon Min (Pelagia Research Library, 2016)
The present review article deals with the deposition technique for the preparation of tungsten oxide films. There are several different methods of deposition were widely used including screen printing method, electrophoretic deposition, thermal evaporation, pulsed laser deposition method, sol gel spin coating deposition, radio frequency reactive magnetron sputter deposition and chemical bath deposition technique as described by many researchers. Xray diffraction was used to determine the structure of obtained films. The X-ray diffraction patterns indicate that the as-deposited films and annealed films are amorphous and crystallite, respectively.